Neutrophil-to-lymphocyte ratio predicts parenchymal hematoma after mechanical thrombectomy in basilar artery occlusion - Hao, Yonggang; Hu, Zhizhou; Zhu, Xiurong; Chen, Zhao; Jiang, He; Lei, Yang; Liao, Jiasheng; Lv, Kefeng; Wang, Kuiyun; Wang, Hongjun; Liao, Jiachuan; Zi, Wenjie; et al. (Frontiers in Neurology, 2022)
Background parenchymal hematoma (PH) is a severe complication of endovascular treatment (EVT) for acute basilar artery occlusion (ABAO). This study aimed to evaluate the incidence and predictors of PH after EVT for ABAO. Methods Using data from the Endovascular Treatment for Acute Basilar Artery Occlusion Study, we enrolled patients treated with mechanical thrombectomy from the BASILAR registry. PH was assessed in accordance with the Heidelberg Bleeding Classification. Logistic regression was used to identify predictors of PH. Results A total of 639 patients were included. Forty-eight patients (7.5%) were diagnosed with PH within 48 h of EVT. Ninety-day mortality was higher in patients with PH compared with those without (81.3 vs. 42.8%, P < 0.001). Favorable neurological outcomes (modified Rankin scale score, 0–3) rates was lower in patients with PH compared with those without (6.3 vs. 34.5%, P < 0.001). With a multivariate analysis, hypertension [odds ratio (OR) = 2.30, 95% confidence interval (CI) 1.04–5.08], pre-treatment National Institutes of Health Stroke Score (NIHSS, >25; OR = 3.04, 95% CI 1.43–6.45), and Neutrophil-to-lymphocyte ratio (NLR, >10; OR = 1.88, 95% CI 1.02–3.48) were associated with PH after EVT. Conclusions PH occurred at a rate of 7.5% after EVT in patients with ABAO. Hypertension, higher baseline NIHSS, and higher NLR value increase the risk of PH after EVT for ABAO.